Analisis Permasalahan dan Kebutuhan Pengembangan Keprofesian Berkelanjutan Guru Smk Bidang Keahlian Bisnis dan Manajemen Pascasertifikasi di Kota Semarang - Wuryandini, Endang (Muhammadiyah University Press, 2014)
The aim of this research was conducted to identify the problems and needs of vocational teachers of business and management pascasertifikasi in Semarang for conducting sustainable professional development to improve professionalism. This study used a qualitative research approach. The subjects in this study were vocational teachers of Business and Management in Semarang Pascasertifikasi totaled 191 teachers consists of 77 teachers of Civil Servants (PNS) and 114 private teachers. Determination of the source of the data is done by sampling purposive. Technique of data gathering used are triangulation, in-depth interviews, documentation, and open questionnaire. Data analysis technique using data interaction analysis model is to collect the data, reducing the data, collate data reduction and data ferivikasi with Focus Group Discution (FGD). The results showed a small proportion of teachers have implemented the appropriate sustainable professional development minimum of credits score and most of the teachers have executed agreements but do not meet all the sub-elements of Sustainable professional development and credit score has not complied with the minimum of credits score required.